Sleep disorders in cirrhotics; How can we detect ?. (6th March 2014) - Gencdal, Genco; Gunsar, Fulya; Meral, Cenk E.; Salman, Esin; Gürsel, Berna; Oruç, Nevin; Karasu, Zeki; Ersöz, Galip; Akarca, Ulus Salih
Abstract Background & Aims Sleep disorders (SDs) are common in cirrhotics and are often associated with hepatic encephalopathy. SDs negatively affect patients' daily activities and work efficiency. For this reason, early diagnosis is important. The methods used for diagnosis of SDs are not practical and need longer periods of application and evaluation. In this study, we aimed to investigate sleep disorders and related clinical parameters in cirrhosis and also wanted to investigate the using of Sleep Timing and Sleep Quality Screening questionnaire (STSQS), a simple form with a short application time, for diagnosis of SDs and its correlation with Pittsburg Sleep Quality Index (PSQI) form. Methods Cirrhotic patients and age‐matched healthy volunteers were enrolled. Patients were excluded from this study if they had neuropsychiatric disease or used excessive alcohol or drugs known to affect sleep. Both groups completed validated Turkish form of PSQI and STSQS. SD was defined as PSQI score (0–21) of >5 or STSQS ≥5. Results One hundred and thirty‐one cirrhotic patients and 18 healthy volunteers were enrolled. SDs in cirrhotics and control group were detected 56.5% and 27.8% by PSQI, 49.6% and 16.7% by STSQS respectively. SDs are the most frequent in the Child C patients, and the least frequent in the Child A patients (P > 0.05). No correlation was found between the MELD score and SDs. SDs were more common in cirrhotic patients with hypoalbuminaemia and low haemoglobin levels. In addition, the patients with decompensated cirrhosis had more frequently SDs than the patients with compensated cirrhosis. In the patient group, sleep latency and total sleep time, sleep parameters were correlated with SDs. STSQS had statistical significant correlation with PSQI for diagnosis of SDs. Conclusion SDs are common in cirrhotics and STSQS could be an appropriate and practical method for diagnosis of SDS in these patients. We can use it in cirrhotic patients at outpatient clinics.